Relationship between gestational anemia and body mass index - Amir Ali Akbari, S; Toghiry, M; Alavi Majd, H (Advances in Nursing & Midwifery, 2010)
Background and aim Anemia is the most common nutritional deficiency in women at reproductive age. In spite of taking iron and folic acid during pregnancy, women suffer from it with a high incidence. Obesity has been suggested as one of causative factors of anemia in recent studies. The aim of this analytical study was to determine the relationship between anemia and body mass index (BMI) before gestation in women before pregnancy referring to Fatemieh Health Center affiliated to Hamadan University of Medical Sciences in 2007. Materials and methods 159 women selected with purposive sampling were divided in terms of hemoglobin levels at 38-40 weeks of gestation into 2 groups (70 anemic, less than 11gr/dl and 89 normal, equal or more than 11gr/dl). BMI was calculated in terms of weight before the 8th week of gestation in kilogram and height in meter. Both groups were matched for intervening variables. Mann-Whitney and chi-square tests were used for data analysis. Data were analyzed by SPSS 13. Findings A significant difference was found in the hemoglobin levels of the groups, i.e. 1 unit increase of BMI would increase the likelihood of anemia 1.6 times (CI=%95, 1.2 to 1.9 times)(P>0.001). Conclusion Obesity may be a risk factor leading to gestational anemia. Keywords: Anemia, Body mass index (BMI), Gestation. *Corresponding Author: Sedigheh, Amir AliAkbari. Lecturer, Dept. of Midwifery, Faculty of Nursing and Midwifery, Shahid Beheshti Universityof Medical Sciences, Tehran, Iran. E-mail:Asa_akbari@yahoo.com